2023
DOI: 10.1007/s00432-023-05504-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of prognostic indicators in patients with head and neck malignancy treated with immune checkpoint inhibitors

Dengxiong Kang,
Siping Liu,
Xin Yuan
et al.

Abstract: Introduction: Tumor immunotherapy has recently emerged as a crucial focal point in oncology treatment research. Among tumor immunotherapy approaches, tumor immune checkpoint inhibitors (ICIs) have attracted substantial attention in clinical research. However, this treatment modality has bene tted only a limited number of patients. We conducted a meta-analysis of various biomarkers to decipher their prognostic implications in patients with head and neck squamous cell carcinoma (HNSCC) who are treated with ICIs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Systematic reviews and meta-analyses have provided evidence that high baseline neutrophil count or high NLR were independently associated with adverse overall survival in various types of solid tumors ( 84 , 117 , 118 , 145 151 ), while normalization of post-treatment NLR was associated with improved survival ( 84 ). Moreover, systematic reviews and/or meta-analyses examining the correlation between NLR and outcomes in patients treated with immune checkpoint inhibitors have reported that higher NLR is a prognostic factor of worse disease control rate, objective response rate, progression-free survival, and/or overall survival in patients with head and neck squamous cell carcinoma ( 152 , 153 ), gastric carcinoma ( 154 , 155 ), melanoma ( 156 ), metastatic renal cell carcinoma ( 157 , 158 ), non-small cell lung carcinoma ( 159 ), hepatocellular carcinoma ( 160 ) and cancer patients in general ( 161 163 ). High post-treatment NLR has also been associated with poor survival outcomes in cancer patients treated with immune checkpoint inhibitors ( 162 ).…”
Section: A High Neutrophil-to-lymphocyte Ratio Is An Independent Prog...mentioning
confidence: 99%
“…Systematic reviews and meta-analyses have provided evidence that high baseline neutrophil count or high NLR were independently associated with adverse overall survival in various types of solid tumors ( 84 , 117 , 118 , 145 151 ), while normalization of post-treatment NLR was associated with improved survival ( 84 ). Moreover, systematic reviews and/or meta-analyses examining the correlation between NLR and outcomes in patients treated with immune checkpoint inhibitors have reported that higher NLR is a prognostic factor of worse disease control rate, objective response rate, progression-free survival, and/or overall survival in patients with head and neck squamous cell carcinoma ( 152 , 153 ), gastric carcinoma ( 154 , 155 ), melanoma ( 156 ), metastatic renal cell carcinoma ( 157 , 158 ), non-small cell lung carcinoma ( 159 ), hepatocellular carcinoma ( 160 ) and cancer patients in general ( 161 163 ). High post-treatment NLR has also been associated with poor survival outcomes in cancer patients treated with immune checkpoint inhibitors ( 162 ).…”
Section: A High Neutrophil-to-lymphocyte Ratio Is An Independent Prog...mentioning
confidence: 99%